Scientific thinking vs. free speech: introducing the Cascade model for justifying research-based learning to faculty - Mieg, Harald A.; Horrer, Anna; Berndt, Markus; Deicke, Wolfgang; Dinter, Joachim; Gess, Christopher; Purrer, Anna; Reichow, Insa; Rueß, Julia; Sailer, Maximilian; Stang, Teresa M.; Fischer, Martin R.; et al. (Frontiers in Education, 2026)
Research-based learning (RBL), promoting an enhanced research-teaching nexus, is a pedagogical approach that has been gaining ground in universities worldwide since the 1990s. What arguments could be used to convince university teachers to RBL into their teaching? In this paper, we try to provide answers by introducing the Cascade Model for justifying RBL, which links RBL to research on epistemic cognition. The model is based on a synthesis of findings from a research network on RBL in the context of higher education reforms in Germany. These findings indicate that a mere focus on teaching formats is not sufficient for the successful implementation of RBL. Rather, the research must be meaningful to those involved - students and faculty alike. The Cascade Model for justifying RBL provides meaningful perspectives on RBL by distinguishing epistemic values that faculty might accept to justify RBL. The model suggests an argumentation cascade of possible references to four epistemic values: scientific, professional, skilled, and social. In this cascade, the link between teaching and scholarly research is progressively decreasing. We applied the Cascade Model to an interview study with 40 university teachers. The model’s categories could be reliably assigned to the responses, with “scientific” being the most frequently cited epistemic value. The ranking of values can be empirically substantiated. As predicted, “higher” levels of justification (i.e., closer to “scientific”) correlate with more RBL teaching.